Mechanisms linking height to early child development among infants and preschoolers in rural India. Issue 5 (18th March 2019) - Black, Maureen M.; Yimgang, Doris P.; Hurley, Kristen M.; Harding, Kimberly B.; Fernandez‐Rao, Sylvia; Balakrishna, Nagalla; Radhakrishna, Kankipati V.; Reinhart, Gregory A.; Nair, Krishnapillai Madhavan
Abstract: Stunting has been negatively associated with children's development. We examined the range of height by testing hypotheses: (a) height is positively associated with children's development, with associations moderated by inflammation and (b) home environments characterized by nurturance and early learning opportunities is positively associated with children's development over time and attenuate associations with height. Data included 513 infants (mean age 8.6 months) and 316 preschoolers (mean age 36.6 months) in rural India from a randomized controlled trial of multiple micronutrient powders (MNPs). Measures included height (height‐for‐age z ‐scores based on WHO standards), inflammation (C‐reactive protein concentration >5 mg/L), nurturance (HOME Inventory), child development (Mullens Scales of Early Learning), and inhibitory control (preschoolers). Linear mixed effects models accounting for repeated measures, clustering, and confounders were used to assess associations between height and child development over time (infants: enrollment, 6 and 12 months; preschoolers: enrollment and 8 months). Moderating effects of inflammation and nurturance were tested with interaction terms. Among infants and preschoolers, height and nurturance were positively associated with all domains of child development over time, with the exception of inhibitory control. Among preschoolers, in the presence of inflammation, height was not associated with child development. Among infants, but not preschoolers, a nurturant home environment attenuated significant associations between height with fine motor and receptive language development. The mechanisms associated with children's development over time are multifactorial and include direct and indirect associations among nutrition, health, and the home environment, as supported by the Nurturing Care Framework. Abstract : In low and middle‐income countries, low height or stunting (a marker of chronic undernutrition) is associated with low developmental skills. This study found that in homes characterized by average or below average nurturance and learning opportunities, height was associated with fine motor skills, as expected. In contrast, in homes characterized by above average nurturance and learning opportunities, the association between height and fine motor skills was not significant, suggesting that a nurturant home environment attenuated the association between infants' height and fine motor skills.